Implicaciones jurídicas, sociales y económicas de la pensión familiar, en el sistema de seguridad social colombiano (2013)
The most important objective of this research is to analyze the legal, social and economical implications of the familiar pensions (law 1580 of 2012) in the colombian social security system, in addition to determine the legal, social and economical advantages that offers the familiar pension for spouses or permanent partners and to set up advantages and disadvantages between the general system’s pension and the familiar pension in Colombia. The main content of this paper, is a research of legal court, base in the principal values of a descriptive methodology that contains an analytic order and qualitative approach. The results obtained from the previous study, allow us to make a conclusion, about the legal, social and economical effects that have created the social security system in pensions, in addition, this is a reflection of some of the difficulties and injustices that many colombian people are suffering nowadays. We can also see that with more of the half of the population with terms of poorness and with aberrant figures, this can’t be worst, and also for the acknowledgment and payment of a pension for many sectors would end a feat to achieve it, that’s why the familiar pension comes to balance or to try an equity and this brings the requirements for obtain a pension for the old age, that this would be share with their respective spouses or couples and this would bring a value of the fundamental core in the society that is the family.